An identity threat perspective on why and when employee voice brings abusive supervision - Wu, Lei; Long, Anna; Hu, Chenbang; Xu, Yunpeng (Frontiers in Psychology, 2023)
Abusive supervision has a negative impact on organizational development. Currently, organizations are vigorously promoting employee voice to promote organizational development. It is important to explore the relationship between employee voice and abusive supervision. Drawing from identity threat theory, this study examines theoretical model linking employee voice and abusive supervision. By collecting data from 93 supervisors and 533 subordinates from a company located in China, the results showed that employee voice was positively related to abusive supervision, and leader identity threat mediated such effect. In addition, the supervisor traditionality moderated the relationship between employee voice and leader identity threat, as well as the indirect effect of employee voice on abusive supervision via leader identity threat, such that these effects were stronger for supervisors with high traditionality.